2014
DOI: 10.1111/ijcp.12596
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac safety of tiotropium in patients with COPD: a combined analysis of Holter‐ECG data from four randomised clinical trials

Abstract: BackgroundTiotropium is generally well tolerated; however, there has been debate whether antimuscarinics, particularly tiotropium administered via Respimat® Soft Mist™ Inhaler, may induce cardiac arrhythmias in a vulnerable subpopulation with cardiovascular comorbidity. The aim of this study was to provide evidence of the cardiac safety of tiotropium maintenance therapy.MethodsCombined analysis of Holter electrocardiogram (ECG) data from clinical trials of tiotropium in chronic obstructive pulmonary disease (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Ogale et al reported increased cardiovascular events (44% HF, 28% acute coronary syndrome, 28% dysrrhythmia) associated with the use of ipratropium [133], but these findings were not substantiated in the randomized controlled trials (RCTs) of tiotropium [134][135][136][137]. In the UPLIFT trial, the incidence of AF was similar between tiotropium group and placebo [134].…”
Section: Respiratory System Drugs and Arrhythmiasmentioning
confidence: 99%
“…Ogale et al reported increased cardiovascular events (44% HF, 28% acute coronary syndrome, 28% dysrrhythmia) associated with the use of ipratropium [133], but these findings were not substantiated in the randomized controlled trials (RCTs) of tiotropium [134][135][136][137]. In the UPLIFT trial, the incidence of AF was similar between tiotropium group and placebo [134].…”
Section: Respiratory System Drugs and Arrhythmiasmentioning
confidence: 99%
“…21 In another study, combined analysis of all trials from the tiotropium clinical trial database involving Holter-ECG monitoring in patients with COPD did not demonstrate any clinically relevant differences between Respimat and HandiHaler with respect to changes in heart rate or in the proportion of patients experiencing supraventricular or ventricular premature beats while on tiotropium. 22 Finally, a pooled analysis of AE data from 28 randomised trials of HandiHaler and seven Respimat studies did not indicate a significantly increased risk of fatal AEs or fatal/non-fatal MACE with either inhaler versus placebo. 23…”
Section: Discussionmentioning
confidence: 92%
“…2015;10:239–59 [ 30 ] Pooled analysis of adverse event data from 28 HH and 7 RMT studies FEV 1 ≤ 70% of FVC Mean FEV 1 41% predicted Patients treated: RMT 5 μg ( n = 3282) RMT placebo ( n = 3283) HH 18 μg ( n = 9647) HH placebo ( n = 8343) Safety: AEs Hohlfeld JM, et al Int J Clin Pract. 2015;69:72–80 [ 32 ] Combined analysis of all tiotropium trials in COPD involving Holter ECG monitoring and conducted between 2003 and 2012 FEV 1 ≤ 70% of FVC NR 4 trials ( n = 727) HH 18 μg RMT 1.25–10 μg Safety: incidence of cardiac arrhythmias Tashkin D, et al Eur Respir J. 2014;44 Suppl 58:923 [ 35 ] Safety analysis in patients with renal impairment included in placebo-controlled trials of once-daily tiotropium Respimat® 5 μg (7 trials) or tiotropium HandiHaler® 18 μg (15 trials) COPD and renal impairment NR n = 10,753 evaluable patients Normal renal function, mild and moderate renal impairment (respectively): HH 18 μg ( n = 860), (n = 1099), ( n = 448) HH placebo ( n = 700), (n = 815), ( n = 347) RMT 5 μg ( n = 1104), (n = 1479), ( n = 662) RMT placebo ( n = 1040), ( n = 1539), ( n = 660) Safety: AEs Verhamme K, et al Eur Respir J.…”
Section: Resultsmentioning
confidence: 99%
“…The issue of whether inhaled anticholinergics and, in particular, tiotropium administered by Respimat®, may induce cardiac arrhythmias in a vulnerable subpopulation with cardiovascular morbidity has been discussed in the literature [ 39 , 46 , 49 ]. In this context, the results of a combined analysis of all tiotropium (HandiHaler® 18 μg and/or Respimat® 1.25–10 μg) trials in COPD involving Holter electrocardiogram (ECG) monitoring, and conducted between 2003 and 2012 [ 32 ], are important. In the four trials that were included in the analysis, patients were required to have a diagnosis of COPD with FEV 1 ≤ 70% of FVC, were aged ≥40 years and had ≥10 pack-years of smoking history.…”
Section: Resultsmentioning
confidence: 99%